Estimation of post-mortem interval: A comparison between cerebrospinal fluid and vitreous humour chemistry. (November 2015) - Swain, Rajanikanta; Kumar, Adarsh; Sahoo, Jyotiranjan; Lakshmy, R.; Gupta, S.K.; Bhardwaj, D.N.; Pandey, R.M.
Abstract: Accurate estimation of post-mortem interval is of great importance in medico-legal autopsy cases. The present study is intended to compare the accuracy of estimating post-mortem interval from biochemical parameters of vitreous humour and cerebrospinal fluid (CSF). Both the fluids were collected from 100 medico-legal autopsies with known time of death and analysed for potassium, glucose, sodium, calcium, urea and creatinine. The current study found that vitreous humour is a better fluid in comparison to CSF for estimation of post-mortem interval. It is also observed that among the statistically significant parameters in both the fluids, level of potassium and sodium in vitreous humour are giving more accurate results in comparison to their corresponding parameters in CSF while accuracy of glucose is more or less same in both the fluid. Nevertheless potassium concentration in vitreous humour is a single best time honoured parameter to estimate post-mortem interval. Highlights: Levels of K +, Na +, Ca ++, glucose, urea & creatinine between males & females were statistically insignificant. Statistically significant correlation was found between PMI and levels of K +, Na + & glucose in vitreous humour & CSF. Vitreous humour is a better fluid in comparison to CSF for accurate estimation of PMI. Vitreous K + is the single best parameter to estimate PMI.